Marketing relacji jako sposób uzyskiwania przewagi konkurencyjnej przez gospodarstwo agroturystyczne - Perechuda, Kazimierz; Nawrocka, Elżbieta (Relationship Marketing as the Way of Winning Competitive Advantage by Agrotourist Farms, 2006)
The objective of the hereby article is to present opportunities for the application of relationship marketing concept in the activities of agrotourist farms. The first part of the paper is devoted to the basic concept of marketing relations and its application in activities conducted by agrotourist farms. On the basis of empirical studies the authors present the degree to which the concept was implemented in the discussed organisations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 219-225